The Accountability of Business Entity with Sadaqah Concept in the Frame of Eling Sangkan Paraning Dumadi - Selfiah Selfiah; Iwan Triyuwono; Yeney Widya Prihatiningtyas (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2021)
This research aims at formulating the concept of accountability of business entity based on Islamic spiritual values. The Islamic-spiritualist methodology is greatly needed to promote this research’s objective. The mutually integrated Physical Endeavor (IL) and Spiritual Endeavor (IB) were used to collect, reduce, analyze data and formulate the concept. Metaphor of Salah movements was used to analyze physical empirical data and spiritual empirical data. The research result shows that the accountability of business entity with sadaqah concept aims at trapping the stakeholders (humans) in spiritual consciousness by “maximizing sadaqah”, representing the spiritual accountability of business entity management. The spiritual value of love internalized in the concept of spiritual accountability may stimulate other spiritual values (such as: itsar (altruism), volunteerism, willingness, righteousness, honesty, and justice values), thus it may promote the welfare of all stakeholders (God, human, and nature) through distribution of added material (monetary and non-monetary), psychological, and spiritual values. The result of this research may be taken as the base to build sharia accounting concept and theory. In addition, this research may also stimulate stakeholders’ (human) behavior based on spiritual values, particularly spiritual value of love